Are promotion programs needed to establish off-grid solar energy markets? Evidence from rural Burkina Faso - Gunther Bensch; Michael Grimm; Max Huppertz; Jörg Langbein; Jörg Peters (RWI - Leibniz-Institut für Wirtschaftsforschung, 2016)
Off-grid solar electric power is a promising technology for remote regions in rural Africa where expansion of the electricity grids is prohibitively expensive. Using household data from a target region of an off-grid solar promotion program in Burkina Faso, this paper explores the role of quality-verified branded solar home systems (SHS) versus non-branded ones. We find that the adoption rate of non-branded SHS is considerably higher at 36 percent compared to eight percent for branded SHS. We compare potential quality differences as well as the cost-effectiveness of branded and non-branded solar. We show that non-branded SHSs provide a similar service level as branded solar, that they do not fall behind in terms of consumer satisfaction and durability, and that non-branded products are more cost-effective. These findings suggest that promotion programs and branded solar products might not be needed to establish sustainable off-grid solar markets. The challenge however is to reach the very poor who are unable to bring up investment costs for any electricity. – – Netzunabhängige Solarenergie ist eine vielversprechende Technologie für abgelegene Regionen im ländlichen Afrika, in denen der Ausbau von Stromnetzen prohibitiv teuer ist. Anhand von Haushaltsdaten aus der Zielregion eines Solarförderprogramms in Burkina Faso wird in diesem Papier die Rolle von qualitätsgesicherten Haushalts-Solarsysteme ("branded SHS") im Vergleich zu nicht qualitätsgesicherten Systemen ("non-branded SHS") erforscht. Zunächst zeigt sich, dass die Verbreitungsraten von non-branded SHS deutlich höher bei 36 Prozent gegenüber acht Prozent für Marken-Solarsysteme liegen. Wir vergleichen sowohl mögliche Qualitätsunterschiede als auch die Kosteneffizienz von branded und non-branded SHS. Es lässt sich beobachten, dass non-branded SHS ähnliche Energiedienste zu günstigeren Preisen erlauben und dabei in Bezug auf Verbraucher-Zufriedenheit und Haltbarkeit mit branded SHS konkurrieren können. Diese Ergebnisse deuten darauf hin, dass Förderprogramme und Marken-Solarprodukte nicht zwingend benötigt werden, um nachhaltige Solarmärkte in netzfernen Regionen zu etablieren. Die Herausforderung besteht jedoch darin, die ärmsten Schichten zu erreichen, die nicht in der Lage sind, die notwendigen Investitionskosten für einen Stromzugang zu erbringen.
Keywords: D12; D40; O13; O33; Q41; 330; energy access; energy poverty; technology adoption; branded products; cost-effectiveness; rural Africa